Marchantia polymorpha Defense Against Snail Herbivory - Fabian Schweizer; Isabel Monte; Roberto Solano; Philippe Reymond (Plant-Environment Interactions)
ABSTRACT During the course of evolution, higher plants have developed efficient strategies to cope with herbivory from arthropods. Upon perception of herbivore‐derived cues, the jasmonic acid (JA) signaling pathway is activated and triggers the expression of defense genes. The first land plants that arose ca. 500 Mya were bryophytes, including liverworts, and fossil records indicate that they were also exposed to herbivore pressure. Interestingly, recent studies showed that the liverwort Marchantia polymorpha contains a functional JA pathway that protects against insect feeding. However, since the appearance of insects is estimated to have occurred several million years after that of bryophytes, we hypothesized that this pathway could have been used to fend off contemporaneous gastropod feeders. Here, we challenged M. polymorpha with the land snail Helix aspersa and found that neonates grew significantly bigger on Mpcoi1, a mutant in the JA pathway, than on wild‐type plants. This finding demonstrates that JA‐dependent defenses in a liverwort are effective against gastropod herbivory and suggests that this feeding group constitutes an additional selection pressure that may have arisen early during land plant evolution.